Feedback in writing production: an analysis of students' perceptions in a Chilean school context (Innovaciones Educativas, 2024)
Feedback allows students not only to recognize their learning gaps, but also to work on them in order to achieve the expected results. Given its relevance, this study addresses the lack of effective feedback in writing processes, especially in the primary and secondary school contexts in Chile. The main objective is to analyze the perceptions of seventh grade language and literature students regarding feedback after the implementation of a pedagogical strategy. Twenty-three students from a Chilean school were interviewed before and after the intervention, which included quantitative and qualitative data. The results showed significant changes in students' perceptions of the value of feedback, its reflective potential, and the encouragement of participation. These findings support the need to incorporate effective feedback strategies into school settings, to integrate them into lesson planning, and to develop concrete activities that encourage their implementation.
Keywords: Feedback; writing; Strategy; Perception; Evaluation; Written production